Out of sight out of mind: Psychological distance and opinion about the age of penal majority - Caldas, Ivete Furtado Ribeiro; Paim, Igor de Moraes; Leite, Karla Tereza Figueiredo; de Mello Junior, Harold Dias; Bataglia, Patrícia Unger Raphael; Martins, Raul Aragão; Pereira, Antonio (Frontiers in Psychology, 2022)
The growth of urban violence has led citizens to demand more severe and punitive measures to solve the problem of juvenile crime in Brazil. One of the current proposals is to reduce the age of penal majority (APM) from 18 to 16 years. We hypothesize that opinion about the proposal to decrease the APM is constrained by construal levels and psychological distance. Thus, we should expect that the knowledge and proximity to the circumstances associated with juvenile transgres-sion will weigh on individual’s opinions about the proposal. To test the hypothesis, we compared responses of two distinct samples composed of passersby in a public square and workers in a ju-venile justice court. After collecting socioeconomic information and their answer to moral di-lemmas the data was analyzed with conventional statistic measures. Our findings suggest that opinion about the APM depends on psychological distance and socioeconomic variables may in-fluence the average construal level of adolescent transgressors in the public’s perspective.